Regulation of natriuretic peptide receptor-A gene expression and stimulation of its guanylate cyclase activity by transcription factor Ets-1. Issue 1 (16th January 2009) - Kumar, Prerna; Bolden, Gevoni; Arise, Kiran K.; Krazit, Stephen T.; Pandey, Kailash N.
Abstract : ANP (atrial natriuretic peptide) exerts its biological effects by binding to GC (guanylate cyclase)-A/NPR (natriuretic peptide receptor)-A, which generates the second messenger cGMP. The molecular mechanism mediating Npr1 (coding for GC-A/NPRA) gene regulation and expression is not well understood. The objective of the present study was to elucidate the mechanism by which Ets-1 [Ets (E twenty-six) transformation-specific sequence] contributes to the regulation of Npr1 gene transcription and expression. Chromatin immunoprecipitation and gel-shift assays confirmed the in vivo and in vitro binding of Ets-1 to the Npr1 promoter. Overexpression of Ets-1 enhanced significantly Npr1 mRNA levels, protein expression, GC activity and ANP-stimulated intracellular accumulation of cGMP in transfected cells. Depletion of endogenous Ets-1 by siRNA (small interfering RNA) dramatically decreased promoter activity by 80%. Moreover, methylation of the Npr1 promoter region (−356 to +55) reduced significantly the promoter activity and hypermethylation around the Ets-1 binding sites directly reduced Ets-1 binding to the Npr1 promoter. Collectively, the present study demonstrates that Npr1 gene transcription and GC activity of the receptor are critically controlled by Ets-1 in target cells.